Immunosenescence as a reason of individualizing immunosuppressive therapy in kidney transplantation - V. A. Fedulkina; A. V. Vatazin; A. V. Kildyushevskiy; A. B. Zulkarnayev; D. V. Gubina; M. P. Fedulkina (Вестник трансплантологии и искусственных органов)
Transplantation in elderly patients is obviously more challenging due to existing underlying diseases, changes in pharmacokinetics of immunosuppressive drugs, polypragmasy, and transformation of immunoreactivity (immunosenescence). Our review presents data on modification of adaptive and innate immunity during aging. It also considers the possibility of both reduced and adapted immunosuppressive therapy in elderly renal transplant recipients in achieving an optimal balance between efficacy and complications.